Sustainability Governance at Universities: Using a Governance Equalizer as a Research Heuristic. Issue 4 (December 2018) - Bauer, Mara; Bormann, Inka; Kummer, Benjamin; Niedlich, Sebastian; Rieckmann, Marco
Abstract Universities play a crucial role in promoting sustainable development. Accordingly, the project "Sustainability at Higher Education Institutions: develop — network — report (HOCHN )" (2016–2018) aims to facilitate sustainable development at universities in Germany. One of the project's research focuses is sustainability governance. It investigates the variety of different protagonists and structures that are involved in the processes of developing and managing sustainability. To this end, a heuristic technique referred to as the "governance equalizer" is applied. It covers five dimensions that have been adapted for this research: politics, profession, organisation, knowledge and visibility. This paper introduces the concept of the governance equalizer and locates it in the context of sustainability in higher education institutions. Against this backdrop, it presents and discusses findings from preparatory expert interviews on sustainability governance, with the aim of validating the governance equalizer and identifying focal points for subsequent stakeholder interviews in German universities.